1992
DOI: 10.1002/eji.1830220922
|View full text |Cite
|
Sign up to set email alerts
|

The induction of resting B cell differentiation does not require T cell contact

Abstract: A T cell clone as well as immediately ex vivo CD4+ lymph node T cells are shown to support the differentiation of co-cultured resting B cells in the absence of T cell-B cell contact. Antibodies specific for class II products of the major histocompatibility complex inhibit the transactivation of resting but not activated B cells. This differential inhibition pattern indicates that the responses obtained from resting B cell populations are not due to their contamination with B cell blasts. Further, supernatants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Spleen cell suspensions were T-cell depleted by treatment with an anti-T-cell mixture together with a 1:40 dilution of baby rabbit complement (Cedarlane Laboratories) as modified from described procedures (10). Flow cytometric analysis showed that <1% of the cells remaining after this treatment were Thy 1+.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spleen cell suspensions were T-cell depleted by treatment with an anti-T-cell mixture together with a 1:40 dilution of baby rabbit complement (Cedarlane Laboratories) as modified from described procedures (10). Flow cytometric analysis showed that <1% of the cells remaining after this treatment were Thy 1+.…”
Section: Methodsmentioning
confidence: 99%
“…T-cell-depleted splenocytes were separated by discontinuous Percoll (Pharmacia) gradients (10). B cells layering at the 1.079/1.085 g/ml (1.079 < p < 1.085) and balanced salt solution (BSS)/1.066 g/ml (p < 1.066) interfaces are designated as resting and activated, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…One explanation for the difference might be that for the C57 mice, both the Tand the B-cell helper epitopes in the VD4 peptide are on the same peptide, whereas for the C3H mice, which are unable to recognize a T-cell helper epitope in the VD4 peptide, these epitopes are on separate molecules. By using in vitro systems it has been shown that epitopes on separate peptides can act together to produce T-cell bystander help for the B cells, as opposed to cognate help, which results when T-and B-cell epitopes are on the same molecule (11,13,32). In cognate help, where there is physical contact between the two cell types, the resulting antibodies have been shown to be of higher affinity than those produced by bystander help (32).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the lower neutralizing response exhibited by the C3H mice in this study could be due to lower-affinity antibodies being produced as a result of the physical separation of the B-and T-cell epitopes. Furthermore, it has been shown with Th1 cell clones that close physical contact is needed for differentiation of B cells due to the weak production of interleukin-5 by Th1 cell clones (13). In contrast, Th2 T-cell clones have been reported to support B-cell differentiation in the absence of contact between T and B cells (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation